US national security Impact on the right to privacy - Ali, Dr. Jamal Taha (The International and Political Journal, 2022)
Although the word privacy is didn’t included in the United States constitution , The Supreme Court in (Katz v. United States) has found that this right to privacy appears in the meaning of 4th amendment , but that didn’t prevent the executive authority to violate this right , and that led the congress to enact ( Foreign Intelligence Surveillance Act ) to protect United States citizens from the executive invasion their privacy , and the executive keep trying to violate this privacy and achieved that after 11/September by enact patriot act .